Go wide or go deep: Margins of new trade flows - Katharina Erhardt; Apoorva Gupta (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2024)
This paper aims to understand the pathways by which exporters become entities that sell multiple goods to multiple customers. To understand firms' export strategies, we analyse new trade flows - new seller-buyer-product combinations - of individual exporters. Our first finding highlights that these new trade flows are an important margin for firms of all size classes, accounting for approximately 62% of their overall trade flows. Classifying new trade flows into going-wide (introducing new products) and going-deep (reaching new buyers for existing products), we find that the dominant margin of export expansion depends on the size and life-cycle stage of exporters; smaller firms rely relatively more on going-wide and large firms more on going-deep. We also demonstrate that selling new products is different from selling existing products: Firms target new products to a single, often new, buyer. To rationalize these facts, we propose a conceptual framework where firms allocate scarce sales personnel between selling existing products to more buyers and matching with new buyers for introducing new products. We empirically test and confirm the model's key predictions. In particular, we use the 2015 Swiss exchange rate shock and show that going-deep is more pronounced as an export strategy when a firm's effective market size is relatively larger. The findings suggest varying scope and size for firms born in different phases of globalisation.
Keywords: F10; F14; L25; O31; 330; Export strategies; product introduction; customer accumulation; buyer-seller relationships; multi-product firms